2011
DOI: 10.1038/bjc.2011.442
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase genetic polymorphisms and toxicity to 5-FU-based chemoradiation in rectal cancer

Abstract: Background:There is a large degree of variation in tumour response and host toxicities associated with neoadjuvant chemoradiation for rectal cancer patients. We performed a complimentary pharmacogenetic study to investigate germline polymorphisms of genes involved in 5-fluorouracil (5-FU) and irinotecan pathways and their potential association with clinical outcomes and toxicities from neoadjuvant chemoradiation in patients with rectal cancer treated in a prospective genotype-directed study.Methods:The germlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 48 publications
(64 reference statements)
1
38
2
1
Order By: Relevance
“…SNP-based toxicity risk has been studied using both candidate gene and genome-wide association approaches [95,96]. To date, the use of SNPs as mucositis risk predictors has been evaluated in a relatively small number of studies [95,[97][98][99][100][101]. Most of these studies are not confirmed and are predominantly associated with metabolic pathways of a small number of drugs.…”
Section: Advances In Mucosal Injury Risk Predictionmentioning
confidence: 99%
“…SNP-based toxicity risk has been studied using both candidate gene and genome-wide association approaches [95,96]. To date, the use of SNPs as mucositis risk predictors has been evaluated in a relatively small number of studies [95,[97][98][99][100][101]. Most of these studies are not confirmed and are predominantly associated with metabolic pathways of a small number of drugs.…”
Section: Advances In Mucosal Injury Risk Predictionmentioning
confidence: 99%
“…9, 11, 14, 1621 However, few studies have examined this association in patients with rectal cancer. 22, 23 …”
Section: Introductionmentioning
confidence: 99%
“…We reviewed the titles and abstracts of all the 146 articles and excluded 80; full texts and data integrity were also reviewed and 59 articles were further excluded. Finally, seven clinical cohort studies with a total of 815 CRC patients met our inclusion criteria for qualitative data analysis (Marcuello et al, 2006;Ruzzo et al, 2008;Braun et al, 2009;Glimelius et al, 2011;Thomas et al, 2011;Budai et al, 2012;van Huis-Tanja et al, 2013). Publication years of the eligible studies ranged from 2006 to 2013.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Currently, common polymorphisms (1298 A > C and 677 C/T) in the MTHFR gene have been reported to be closely associated with the toxicity and clinical responses of irinotecan-based chemotherapy in CRC patients (Glimelius et al, 2011;van HuisTanja et al, 2013). Nevertheless, contradictory results were also reported in many other studies (Braun et al, 2009;Thomas et al, 2011). Therefore, we performed this metaanalysis to evaluate the effects of common polymorphisms in the MTHFR gene on the toxicity and clinical responses of irinotecan-based chemotherapy in CRC patients.…”
Section: Introductionmentioning
confidence: 97%